On Teaching Old Dogs New Tricks. (December 2015) - Metcalfe, Janet; Casal-Roscum, Lindsey; Radin, Arielle; Friedman, David
Although older adults rarely outperform young adults on learning tasks, in the study reported here they surpassed their younger counterparts not only by answering more semantic-memory general-information questions correctly, but also by better correcting their mistakes. While both young and older adults exhibited a hypercorrection effect, correcting their high-confidence errors more than their low-confidence errors, the effect was larger for young adults. Whereas older adults corrected high-confidence errors to the same extent as did young adults, they outdid the young in also correcting their low-confidence errors. Their event-related potentials point to an attentional explanation: Both groups showed a strong attention-related P3a in conjunction with high-confidence-error feedback, but the older adults also showed strong P3as to low-confidence-error feedback. Indeed, the older adults were able to rally their attentional resources to learn the true answers regardless of their original confidence in the errors and regardless of their familiarity with the answers.